AGAMA DAN PENDIDIKAN KARAKTER: PENGEMBANGAN KEILMUAN DAN KOMPETENSI PROGRAM STUDI PADA UIN SUNAN KALIJAGA YOGYAKARTA - Mochammad Fu'ad (Jurnal Pendidikan Agama Islam, 2014)
The problems of the present and future perspectives change IAIN Sunan Kalijaga be UIN will undoubtedly bring new problems, namely how to formulate the curriculum and implementation of education. In the global scale of the problem is always related to the issue of “ten educational issues of the future” as a result of changes in the field of science and technology, economic and demographic, social, cultural, and religious. By way of putting this issue will be developed research that questioned whether functionally-paedagogis UIN could produce improved inter-generational and intra-generational Muslim personality, the ability of science, technology and art, as well as spirited interpreneurship (skills for independent living).Religion and character education seems to be the cornerstone of this program of education and the learning process in UIN Sunan Kalijaga Yogyakarta. Changes that occur in the real UIN Sunan Kalijaga is a change in the college of the Institute into a university. The changes are made to declare a new paradigm and conducted a study of the religious sciences and general sciences, ie interconnect integration paradigm. This paradigm requires the effort to dialoging openly and intensive educational development Qur’anic perspective, the program and the whole educational process between the study of Scripture (hadlarah an-nas), scholarly study (hadlarah al-ilm), and are concerned with the territory implementation, real praxis in reality and ethics (hadlarah al-falsafah).